Characterization of Tensile Properties of Piassava Fiber Reinforced Polyester Composites - Denise Cristina Oliveira Nascimento; Isabela Leão Amaral da Silva; Alice Barreto Bevitori; Felipe Perissé Duarte Lopes; Sergio Neves Monteiro (The Minerals, Metals and Materials Society, 2011)
"The piassava fiber is one of the most rigid natural lignocellulosic fibers, which has since the last decade been investigated as possible reinforcement for polymeric composites. In the present work, the tensile properties of polyester composites reinforced with piassava fibers with thinner diameters were investigated. Composites with volume fractions up to 30% of continuous and aligned piassava fibers were tensile tested at room temperature to evaluate the ultimate strength, elastic modulus and total strain. For each volume fraction, individually separated fibers with the smaller diameters were tested. The results indicated that the tensile properties tend to improve with increasing volume fraction of the thinner piassava fibers. The role played by the fiber/matrix interaction was analyzed by scanning electron microscopy.IntroductionA significant change in the transportation sectors mainly the aerospace and automotive, occurred last century with the introduction of stronger and lighter materials. The most relevant example was the polymer composite reinforced with synthetic fiber. They are nowadays replacing conventional materials such as the aluminum alloys in airplane body owing to superior specific strength. in recent years, however, environmental problems in a global scale are imposing a reversion in the use of synthetic fiber specially the glass fiber. In spite of its higher specific strength, this fiber and its polymer composites can neither be recycled nor incinerated in a thermal plant to generate electricity [1]. Moreover, the fabrication, processing and transportation of a glass fiber composite are associated with C02emission, the major responsible for global warming [2].A possible substitute for glass fiber without the above-mentioned environmental problems, could be a natural fiber. In fact, natural fibers obtained from cellulose-rich plants, also called lignocellulosic fiber, are already being used in several engineering fields, particularly the automobile industry [3-6]. Figure 1 illustrates an automobile and its many components made of lignocellulosic fiber composite [7]."